OPTIMALISASI PENDAPATAN ASLI DAERAH (PAD) DI DKI JAKARTA MELALUI CUKAI KENDARAAN BERMOTOR - Dwiki Ananto Yudo (Unitri Press, 2019)
This paper aims to examine the source of PAD through motorized vehicle excise tax which can increase regional income in DKI Jakarta. Based on data published by the Badan Pusat Statistik (BPS) of DKI Jakarta Province, in 2015 the number of motor vehicles in DKI Jakarta was 18,668,056 units. From these data it is seen that the potential for regional revenues from motorized vehicles, so that local governments can maximize public services. This paper uses literature study research methods, by analyzing existing data in books, journals, and research institute publications. Based on the results of the study, it can be concluded that the Regional Government of DKI Jakarta may apply the imposition of vehicle excise tax to optimize local revenue through PAD, because there are negative externalities resulting from motor vehicles circulating on roads in the DKI Jakarta area.